FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT DALAM MENGURUS IMB DI KECAMATAN IPUH KABUPATEN MUKO-MUKO - Maryeni, Putri; Rianto, Slamet; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
Poor informed society considers necessary to establish the IMB is not a plus in the administration building permit required to meet the public administration, it is certainly burdensome to low-income communities. But the fact that society is not entirely to blame for the extent permitted building. This study aims to determine the factors that affect the public interest in the care of the IMB in Ipuh District Mukomuko region, seen from socialization, income and distance of residence.The study was descriptive correlational. Population in this research is the head of the family who do not take care of IMB in Ipuh District Mukomuko region, amounting to 1.193 (KK). Samples were taken with a proportional random sampling technique with a proportion of 10% so that the sample amounted to 117 households.The research found that: 1) there is a socializing influence on the public interest in the administration of IMB in Ipuh District Mukomuko region for t > t table (9,494> 1,662), the influence of strong (r = 0,663) and a significant contribution (43,9%), (2) there is no effect on the income level of public interest in the administration of IMB in Ipuh District Mukomuko region for t <t table (-0,598 < 1,662), the strength of the relationship is very small (r = 0,056) and a very small contribution (0,3%), (3) there are significant distances shelter against the public interest in the administration of IMB in Ipuh District Mukomuko region for t > t table (2,171> 1,662), very low power relationship (r = 0,198) and a very small contribution (3,9%) and (4) There is a significant and positive effect of socialization, income level and distance of residence together against the public interest in the administration of IMB in Ipuh District Mukomuko region because F> F table (34,789> 2,712). Three variables influence the magnitude of the public interest in the administration of IMB in Ipuh District Mukomuko region including medium category (r = 0,693) and a significant contribution (48,0%).